Urban and Territorial Resilience. Urbanism Facing Crisis - Cristiano, Silvio; Trabucco, Isabella; Amenta, Libera; Cazzola, Ilaria; Giudice, Benedetta; Pisano, Carlo; Russo, Michelangelo; Vettorato, Daniele; Vingelli, Federica; Voghera, Angioletta (Contesti. Città, territori, progetti, 2026)
Cities and landscapes are undergoing an ever increasing number of often intertwined crises, which urbanism and territorial governance are called to fully understand and to timely and effectively address, in order to protect – in advance and/or in the midst of an emergency – the health and the sound operation of the spatial systems in which human and non-human societies can only live and flourish, i.e. the ecosystems upon which everything depends: the ecological, the social, and the economic spheres, and with them the cultural, the political, etcetera. Spatial multi-risk has been the core of the scientific activities taking place within the Spoke number 5 “Urban and metropolitan settlements” of the extended partnership project “RETURN – multi-Risk sciEnce for resilienT commUnities undeR a chaNging climate”. This special issue brings together studies and perspectives from those scientific activities, connected projects, and topic-relevant parallel studies, expanding much beyond the original idea to collect the proceedings of the special session “Urban and territorial resilience: from measuring to building planning solutions”, organised by most of this issue’s Guest Editors (Amenta, Cazzola, Cristiano, Giudice, Trabucco, & Vingelli) within the 63rd Congress of the European Regional Science Association (Terceira, Portugal, 26–30 August 2024).